Persian Historic Urban Landscapes Interpreting and Managing Maibud over 6000 Years - Esfanjary, Eisa (Edinburgh University Press, 2022)
The first urban study of the Iranian city of Maibud over its 6000-year historyPersian cities are part of a corridor of civilisation with settlements straddling thousands of years. Taking Maibud as a case study, Eisa Esfanjary traces the evolution of ancient settlements chronologically, thematically and methodologically.Maibud provides the basis from which a new interpretive approach is developed, being a city that has a history of several millennia yet has a scale that renders it manageable with archaeological remains that range across several phases of building development. An archetypal example of middle-sized Persian cities, it affords insights into the entire urban landscape and its spatial, functional and morphological iterations. Within this overall picture, a methodology is developed to explore various morphological elements of the city, the three key components of which are the town plan, the building type, and construction materials. The inter-relationships between these three components are explained in order to formulate an approach to support the management and conservation of the historic urban landscape.Combining a rigorous survey and observation of the standing structures with scarce archaeological and written sources, this book sheds light on Islamic urbanism in general and Islamic urbanism in Iran particularly.Key FeaturesOrganised in three main parts: a conceptual framework; the case study of Maibud; and an explanation of its wider significances, and potential policy applicationsSheds new light on the development of one of ancient world's oldest, yet least known, living cities in Iran, supported by highly original and convincing analysisFeatures case studies with new evidence, which require us to re-evaluate our understanding of urbanism not just in Iran but also in the wider Islamic worldIllustrated with many images including maps, plans, line drawings, watercolours and colour photos